"Can you Hear Me Now?" AMPA Receptor-Mediated Tonotopy Disruption by Early Life Seizures. Issue 6 (November 2018) - Velíšek, Libor
Early Seizures Prematurely Unsilence Auditory Synapses to Disrupt Thalamocortical Critical Period Plasticity. Sun H, Takesian AE, Wang TT, Lippman-Bell JJ, Hensch TK, Jensen FE Cell Rep 2018;23:2533–2540. Heightened neural excitability in infancy and childhood results in increased susceptibility to seizures. Such early-life seizures are associated with language deficits and autism that can result from aberrant development of the auditory cortex. Here, we show that early-life seizures disrupt a critical period (CP) for tonotopic map plasticity in primary auditory cortex (A1). We show that this CP is characterized by a prevalence of "silent, " NMDA-receptor (NMDAR)-only, glutamate receptor synapses in auditory cortex that become "unsilenced" due to activity-dependent AMPA receptor (AMPAR) insertion. Induction of seizures prior to this CP occludes tonotopic map plasticity by prematurely unsilencing NMDAR-only synapses. Further, brief treatment with the AMPAR antagonist NBQX following seizures, prior to the CP, prevents synapse unsilencing and permits subsequent A1 plasticity. These findings reveal that early-life seizures modify CP regulators and suggest that therapeutic targets for early post-seizure treatment can rescue CP plasticity.